Sound Information: Sonification in the Age of Complex Data and Digital Audio. - Supper, Alexandra (Information & Culture, 2015)
In recent years, sonification--the auditory display of data--has received increasing media attention and been presented as a solution to the challenges posed by large, complex datasets. By analyzing the development of the sonification research community, this article shows that specific historical configurations have led the community to concentrate on technical solutions for the design of sonification technology rather than on analyzing and interpreting sonified data. Consequendy, sonification still struggles for scientific acceptance and does not offer any ready-made solutions to the problems posed by complex data; indeed, it echoes, rather than solves, these problems.